Respuestas

  • Usuario de Brainly
2013-12-08T16:41:09+01:00
2logx=log2+log(3x-4)

Aplicando propiedades de logaritmos:

logx² = log(2(3x-4))

x² = 2(3x-4)

x² = 6x-8

x² -6x + 8 =0

x² - 4x -2x + 8 = 0

x(x-4) -2(x-4)=0

(x-2)(x-4)=0

x-2=0             ó         x-4=0
x=2               ó           x=4

Conjunto solucion: {2;4}
  • Usuario de Brainly
2013-12-08T21:27:36+01:00
2logx=log2+log(3x-4)
logx²=log2*(3x-4)
x² = 6x - 8
x² - 6x + 8 = 0

x =  \frac{6 \frac{+}{} \sqrt{(-6)^2-4*8*1}}{2}

x =  \frac{6 \frac{+}{} \sqrt{36-32}}{2}

x =  \frac{6 \frac{+}{} \sqrt{4}}{2}

x =  \frac{6 \frac{+}{} 2}{2}

Solución:
x₁ = 4  Válida
x₂ = 2  Válida